Lesbians, Gay Men, Bisexuals, Trans, Inter and Queers*: Some challenges for the theory and work of Bioenergetic Therapists - Heinrich, Thomas (Bioenergetic Analysis, 2019)
Since the International Conference of the IIBA in 2007 at Sevilla, the shift of attitude in the Bioenergetic world towards LGB* to an affirmative one became public. Simultaneously, in the Bioenergetic world the publishing on this topic stopped. The resulting gap to the meanwhile increased knowledge of LGBTIQ* affirmative research will hereby filled up by information about the life situation of LGBTIQ*, an empathetic change of perspective on the LGBTIQ* world and some considerations on a Bioenergetic affirmative approach for the body related psychotherapy with LGBTIQ* clients.